Analysis of Project Success Criteria in the Nigerian Construction Industry - Dosumu, Oluwaseun Sunday; Onukwube, Henry Ndubuisi (International Journal of Sustainable Construction Engineering and Technology, 2013)
This paper examined the relative importance of the project success criteria in the Nigerian construction industry. It also determined the correlation among the project success criteria. Based on the literatures reviewed, the study proposed a framework for measuring project success in the construction industry. The respondents for the study were the government, private clients, consultants and contractors. Three hundred copies of questionnaires were distributed to capture data on the subject, but only 86 were returned and used for the study. The paper captured respondents that are resident in Lagos state, Nigeria and chosen by convenience from selected organizations used for the study. The data were analysed with SPSS 16 through the use of frequencies, mean scores, factor analysis and correlation. Factor analysis was employed because the mean scores showed that all the project success criteria were at least important. Nine principal components were finally merged into 4 through the factor analysis using the Varimax rotation with Keiser normalization. The study found out that all the project success criteria were important but their level of importance differs according to the factor analysis carried out. Therefore, it was concluded that there are four major components of construction project success in Nigeria- user-related factors, professionals’ factors, organisational factors and other minor factors. The minor factors were found to be related to both organizations and projects but were not highly rated by respondents for determining construction project success. The study also concludes that project success criteria goes beyond meeting cost, time and quality target, it includes users’ satisfaction, professionals’ fulfilment and achievement of organizational goals. The recommendation of the study was that for construction projects to be successful, attention must be paid to users’ related factors, professionals’ factors and organizations’ factors.